The perspective of sustainability in networked knowledge society: governance, education, ethics - Pilar AZNAR MINGUET; Mª Pilar MARTÍNEZ AGUT (Ediciones Universidad de Salamanca, 2013)
This article aims to stimulate thinking about entering the perspective of sustainability in new information societies and knowledge supported by ICTs, and characterized by globalization is far from inclusive. It involves the construction of a global system that promotes the pursuit of environmental quality, social justice and an equitable economy and viable long term. UNESCO has identified three basic ways to get it: governance, education and ethics. Governance can promote equitable social connectivity, changes in patterns of production and consumption and application search and real solutions to the socio-environmental. Education can foster continuing education of those critical, responsible and committed attitudes of respect and harmony with the natural and social environment, international organizations like the OECD, UN and governments through the development of their educational systems, have shaped the competency-based training model, including skills for sustainability are key consider. And all from ethical approaches to guide human capacity to think, act and promote the defense of life on our planet.